Sports acrobatics - Ellingsen, Ray; Martin, Jean-Lue; Van Loo Productions (Australia : Van Loo Productions, 2002)
Learn the basic of acrobatics' beautiful and distinctive art form. Increase fitness level, strength and coordination while discovering this unique and exciting movement form
Title from title screen
Executive producer, Christine Van Loo ; camera operators, Mishael Johnson, Rex Blatter
Hosted by Richard Hatch with Jean-Lue Martin, Christine Van Loo
Keywords: Acrobatics; Acrobats and acrobatics; Gymnastics